Strategies to manage volatility in ports - Toh, Wei Ling (Nanyang Technological University, 2022)
External shocks such as COVID-19 can cause ports around the world to face various kinds of volatilities. As ports act as a central pivot for the flow of cargoes from sea to land, it is important to adapt to situations in order to reduce and better manage the impact caused by these shocks. In the case of multipurpose ports, complexity is greater due to the nature of the port business. As they handle various kinds of cargoes, more vehicles and facilities are needed to serve the same volume of throughput as compared to ports that serves homogeneous cargoes such as container ports. In this paper, an Analytical Hierarchy Process (AHP) model was used to assess the strategies to help multipurpose ports manage throughput volatility in face of external shocks like COVID-19. In addition to the identification of strategies that can be adopted by ports, AHP ranks the effectiveness of each strategy. Furthermore, the research has been enhanced by explicitly including ten key stakeholders working in Jurong port. Results have shown that using information technology (IT) such as JAVA and CPLEX as a decision support tool can be a viable method for multipurpose ports.